The pharmaceutical potential of crude ethanol leaf extract of Pedalium murex (L.). (January 2022) - Narayanan, Mathiyazhagan; Kiran, Arunachalam; Natarajan, Devarajan; Kandasamy, Sabariswaran; Shanmugam, Sabarathinam; Alshiekheid, Maha; S. Almoallim, Hesham; Pugazhendhi, Arivalagan
Graphical abstract: Highlights: Pedalium murex ethanol extract contains more numbers of bioactive phytochemicals. First report of P. murex antibacterial activity on bacteria causing skin infections. Antibacterial activity of ethanol extract against bacterial pathogens was excellent. Excellent antioxidant activity was observed against DPPH and Hydroxyl radicals. On the HEK 293 cell line, the ethanol extract had no significant cytotoxic activity. Abstract: The purpose of this study was to determine the antibacterial competence of various solvent leaf extracts of Pedalium murex against bacteria that cause skin infections such as Staphylococcus aureus, (folliculitis), Streptococcus pyogenes (impetigo), and Corynebacterium sp. (pitted keratolysis). The presence of phytochemicals, antioxidant activity, and cytotoxicity on the Human Embryonic Kidney (HEK 293) cell line were also studied. The ethanol extract contained more phytochemical ingredients (saponins, flavonoids, alkaloids, terpenoids, phenolics, quinones, and betacyanin) than the other extracts. An increased concentration of ethanol extract demonstrated excellent antibacterial activity (zone of inhibition) against bacteria such as S. aureus, S. pyogenes, and Corynebacterium sp. and it followed by methanol extract. This is the first report on the antibacterial activity of an ethanol extract of P. murex against bacteria that cause skin infections. The average minimum inhibitory concentration (MIC) value of ethanol extract was found as 13.64 mg mL −1 . In the 2, 2-Diphenyl-1-picrylhydrazyl (DPPH) and hydroxyl free radical scavenging assay, the crude ethanol (87.25 and 83.24 % respectively) and methanol extracts (81.41% and 78.39% respectively) showed excellent antioxidant activity. The cytotoxicity study (4, 5-Dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT assay) revealed that the crude ethanol extract of P. murex effectively supported the proliferation of HEK 293 cell line with the absence of considerable number of cell death even at 500 mg mL −1 . The findings concluded that the components present in the ethanol extract could be used in drug formulations to combat bacteria that cause skin infections without causing side effects.